BUSINESS EFFICIENCY IN THE CONDITIONS OF DIGITALIZATION: MARKETING ASPECT - Мосумова, Айнура Кярам кизи; Пурей, Євген Ю. (Journal of Strategic Economic Research, 2024)
The effectiveness of business in the conditions of digitalization depends on various factors, which include technological innovations, strategic management, digital marketing and adaptation to new realities. Enterprises must implement new technologies and digital innovations to optimize business processes, improve efficiency and ensure competitiveness. Enterprises must be ready to adapt to changes in the technological environment, market conditions and consumer demands. The purpose of the presented work is to determine the main components of business efficiency in the conditions of digitalization. Determine the place of the marketing complex in ensuring the sustainable development and competitiveness of entrepreneurship. The main methods used in the work are: methods of analysis and synthesis to determine the main effective tools of business in conditions of digitalization to ensure its stability on the market, methods of deduction and induction to identify the marketing aspect of the influence on the process of becoming a sustainable business system, a method of comparison for understanding of the process of entrepreneurial activity in traditional languages and in the conditions of digitization and a graphic method for the schematic display of the main results of the conducted research. The main findings of the study are the following aspects: the collection, analysis and use of data are critical for understanding customer needs, forecasting market trends and making informed decisions; the use of business process management tools allows enterprises to increase productivity and implement changes faster; developed digital marketing strategy, presence on the Internet and active interaction in the online environment contribute to attracting customers; companies that implement innovative technologies and practices usually have an advantage in the competitive environment; ensuring the security of digital assets and information is a critically important element of effective business in the conditions of digitalization; development of digital competences in own personnel and attraction of talented specialists; cooperation with other companies, creation of strategic partnerships and participation in digital ecosystems. In general, the effectiveness of business in the conditions of digitalization is determined by the depth and success of the implementation of digital strategies, as well as the readiness to adapt to rapidly changing environmental conditions and market requirements.